2011
DOI: 10.2298/vsp100809001p
|View full text |Cite
|
Sign up to set email alerts
|

The influence of probiotics on the cervical malignancy diagnostics quality

Abstract: The application of probiotic strains Lactobacillus rhamnosus GR-1 and Lactobacillus reuteri RC-14 concomitantly with specific anti-infective agents provides more reliable cytological diagnostics, reduces the number of false positive and false negative findings on cervical malignancy and normalizes vaginal microflora in higher percentage of patients with vaginal infections comapred with therapy including antiinfective agents only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
(14 reference statements)
0
5
1
Order By: Relevance
“…Nevertheless, we only identified one related study in a literature search. Perisic et al reported that the use of Lactobacillus rhamnosus GR-1 and Lactobacillus reuteri RC-14 could decrease the presence of unsatisfactory and/or borderline satisfactory cytological findings and thus provide a more reliable cytological diagnosis [26]. In our hospital, the annual Pap smear unsatisfactory rate is around 2.5%, however in the present study the rate was as high as 7.44%.…”
Section: Discussioncontrasting
confidence: 61%
“…Nevertheless, we only identified one related study in a literature search. Perisic et al reported that the use of Lactobacillus rhamnosus GR-1 and Lactobacillus reuteri RC-14 could decrease the presence of unsatisfactory and/or borderline satisfactory cytological findings and thus provide a more reliable cytological diagnosis [26]. In our hospital, the annual Pap smear unsatisfactory rate is around 2.5%, however in the present study the rate was as high as 7.44%.…”
Section: Discussioncontrasting
confidence: 61%
“…The application of probiotic strains Lactobacillus rhamnosus GR-1 and Lactobacillus reuteri RC-14 concomitantly with specific anti-infective agents provides more reliable cytological diagnostics, reduces the number of false positive and false negative findings on cervical malignancy and normalizes vaginal microflora in higher percentage of patients with vaginal infections compared with therapy including anti-infective agents only [49].…”
Section: Treatment and Prevention: Microbiota-derived Factorsmentioning
confidence: 99%
“…Lactobacillus rhamnosus GR-1 and Lactobacillus reuteri RC-14 are two probiotic strains which have shown desirable effects on gynecological diseases [109,110]. Evidence suggests that using Lactobacillus rhamnosus GR-1 and Lactobacillus reuteri RC-14 along with antiinfective agents leads to a reduction in false negative and false positive results of cervical malignancies; thus, cytological diagnoses are more reliable with this method [111]. Compared to when using anti-infective drugs alone, applying these probiotic strains provide a higher percentage of vaginal microflora normalization in patients who have vaginal infection [111].…”
Section: Probiotics Provide a Better Diagnosis Of Cervical Cancermentioning
confidence: 99%
“…Evidence suggests that using Lactobacillus rhamnosus GR-1 and Lactobacillus reuteri RC-14 along with antiinfective agents leads to a reduction in false negative and false positive results of cervical malignancies; thus, cytological diagnoses are more reliable with this method [111]. Compared to when using anti-infective drugs alone, applying these probiotic strains provide a higher percentage of vaginal microflora normalization in patients who have vaginal infection [111]. A study investigated the impacts of probiotic strains on the quality of cervical smear and clearance of genital high-risk human papilloma virus [112].…”
Section: Probiotics Provide a Better Diagnosis Of Cervical Cancermentioning
confidence: 99%